Diffusion tensor magnetic resonance imaging for single subject diagnosis in neurodegenerative diseases - Sajjadi, Seyed A.; Acosta-Cabronero, Julio; Patterson, Karalyn; Diaz-de-Grenu, Lara Z.; Williams, Guy B.; Nestor, Peter J. (Brain (London, England : 1878), 2013)
Although magnetic resonance imaging is a standard investigation in neurodegenerative disease, sensitive and specific markers for the underlying histopathological diagnosis are largely lacking. This report presents evidence to indicate that corticobasal degeneration and progressive supranuclear palsy, in particular, might be identifiable at a single subject level with diffusion tensor imaging. Patients with clinical diagnoses of Alzheimer's disease, semantic dementia and non-fluent primary progressive aphasia (n = 9 each) were contrasted with control subjects (n = 26) with the diffusion tensor imaging measures: fractional anisotropy, axial and radial diffusivity. At 1 year follow-up, all participants with non-fluent primary progressive aphasia had evolved either corticobasal degeneration (n = 5) or progressive supranuclear palsy (n = 4). The corticobasal degeneration/progressive supranuclear palsy set showed white matter abnormalities involving the entire cerebrum. Individual maps were similar to the group level results, even in the most minimally impaired patients. Fractional anisotropy was consistently the most sensitive metric. In Alzheimer's disease and semantic dementia, by contrast, group level and individual analyses revealed limited areas of abnormality centred on the posterior cingulate and rostral temporal lobes, respectively. In both groups radial diffusivity was the most sensitive metric. Scrutiny of the standard scores for each group's most sensitive metric revealed that, although the values for every patient with corticobasal degeneration or progressive supranuclear palsy fell outside 95% of the normal mean, none of the other two groups' members had values outside this range. Further underscoring the hypothesis that this finding relates specifically to a diffuse pathological process in the white matter of the tauopathies, and is not merely a function of disease severity, a grey matter analysis consisting of group level voxel-based morphometry revealed only focal areas of atrophy in all three groups. Consistent with past reports for the respective clinical syndromes, these were centred on the left frontal operculum and caudate nucleus in non-fluent primary progressive aphasia (the corticobasal degeneration/progressive supranuclear palsy set), anterior temporal lobes in semantic dementia, and hippocampus and posterior cingulate gyrus in Alzheimer's disease. Detection of this extensive white matter lesion in corticobasal degeneration and progressive supranuclear palsy-a pathologically proven feature of these conditions--in single subjects with diffusion tensor imaging appears to have strong diagnostic marker potential for these diseases.